Dosa Dan Kewajiban Agama Dalam Catur Yuga Menurut Parāśara Dharmaśāstra - I Putu Ariyasa Darmawan (Pramana: Jurnal Hasil Penelitian, 2022)
The Dharmaśāstra is considered the most important and interesting of the many śāstra books which contain the basic set of Hindu teachings and is known as one of the Vedaṅga books, namely the body part of the Vedas which cannot be separated from other Veda Śruti books. Dharmaśāstra is one of the Vedāṅgas and has the most important meaning and position in Hindu society. It consists of Śikṣa, Vyākaraṇa, Chanda, Nirukta, Jyotiṣa and Kalpa. The most important type of Vedāṅga and which has something to do with this Dharmaśāstra book is the Kalpa type. The origin of this Kalpa book is sourced from the Brāhmaṇa saṁhitā and is written in the form of a sūtra or śloka. Based on their usage, this group of Kalpa vedāṅga consists of four types according to their respective topics. The laws of Mānu were enacted during the time of Satya; the law of Gautama in the time of Tretā; the laws of Śaṅkha and Likhita during the time of Dvāpara; and the law of Parāśara in the Kaliyuga.Strict observance of penance (tapa) was a virtue during the Satyayuga; knowledge of the self (jñana) in the Tretāyuga; performing religious sacrifices (yajña) during the Dvāparayuga period, and performing almsgiving (dānam) during the Kaliyuga period. Kāliyuga means the age of strife marked by the fading of the spiritual life, because the world is fettered by material life. Human orientation is only on pleasure by satisfying sensual desire (Kāma) and if this continues to be followed, then lust is like a fire doused with kerosene or gasoline, it will not go out, but destroys the human being. The characteristics of the Kāli era (Kāliyuga) are increasingly evident in the era of globalization which is marked by the rapid flow of information, driven by technological developments with the content of the philosophy of Hedonism which is only material oriented and attempts to obtain mere pleasures